The potential for dense medium separation of mineral fines using a laboratory Falcon Concentrator. (1st May 2017) - Marion, C.; Williams, H.; Langlois, R.; Kökkılıç, O.; Coelho, F.; Awais, M.; Rowson, N.A.; Waters, K.E.
Highlights: Laboratory scale Falcon concentrator adapted to run as a batch centrifugal dense medium separator. Sub 10 μm minerals have been separated. Zircon upgrade ratio of 4.39 obtained, higher than a conventional centrifuge. Potential application to treating mineral slimes which otherwise would be discarded. Abstract: Dense medium separation (DMS) is a technique used to separate particles based on specific gravity. Conventional DMS is, however, limited to coarse particle sizes and is not practical when processing fines. To improve the separation efficiency when processing fine particles, centrifugal separators have been employed. This work investigates DMS in a lab centrifuge and a modified Falcon Concentrator, in order to process the slimes of a rare earth ore. It has been shown that centrifugal concentration using a dense medium is possible when recovering values from a slimes fraction. Both the lab centrifuge and modified Falcon Concentrator result in a similar performance.